Dynamical evolution of escaped plutinos, another source of Centaurs - Di Sisto, Romina Paula (2010)
Context. Weakly chaotic orbits that diffuse very slowly have been found to exist in the plutino population. These orbits correspond to long-term plutino escapers and represent the plutinos presently escaping from the resonance. Aims. We perform numerical simulations to explore the dynamical evolution of plutinos that have recently escaped from the resonance. Methods. The numerical simulations were divided into two parts. In the first, we evolved 20? 000 test particles in the resonance to detect and select the long-term escapers. In the second, we numerically integrated the selected escaped plutinos to study their dynamical post escaped behavior. Results. We characterize the escape routes of plutinos and their evolution in the Centaur zone. We derive a present rate of escape of plutinos of between 1 and 10 every 10 years. The escaped plutinos would have a mean lifetime in the Centaur zone of 108 Myr and their contribution to the Centaur population would be a fraction of smaller than 6% of the total Centaur population. In this way, escaped plutinos would be a secondary source of Centaurs.